Mitos Dalam Film Si Kabayan Berjudul "TARUHAN" Karya Didi Petet - Iwan Muhammad Ridwan (ArtComm, 2019)
The research entitled "Myths in the Si Kabayan Film Titled Didi Petet's Betting" aims to uncover a number of myths that actually occur in Sundanese society and analyze them about Roland Barthes's semiotic approach to the meaning of denotation and connotation. In the film Si Kabayan: Bet there are a number of myths which are a blend of myths that have lived in society and myths that were created by Si Kabayan's ingenuity. Si Kabayan's figure is always identified with the character of silly, lazy, but a lot of sense that can often defeat the antagonist he faces. Likewise, this film was produced in 1991. The Kabayan can fool the characters who become antagonists for himself with a number of myths he made. Even so, interpreting the myths that are found in the film Si Kabayan: Bets are needed interpretations from the people who live in Si Kabayan's living environment, because a number of these myths are mostly special myths that are rarely heard in real life. Some myths can also be broken by Si Kabayan himself.